Исследование температурного поля накопителя на жестких магнитных дисках - Nikolaenko, Yu. E.; Kravets, V. Yu.; Grabovsky, V. S. (PE "Politekhperiodika", Book and Journal Publishers, 2003)
The paper presents the results of analyzing the temperature field of Maxtor Diamond Max Plus 9, 60 GB ATA/133 HDD in six typical operating modes. It was found that in all studied modes the most heated elements of the drive are the microcircuits of the electronic unit. Recommendations are provided for organizing heat removal from the heated zones.